2022
DOI: 10.1177/17590914211073381
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Long-Term Human iPSC-Derived Spinal Motor Neuron Culture Using a Dendritic Polyglycerol Amine-Based Substrate

Abstract: Human induced pluripotent stem cells (hiPSCs) derived from healthy and diseased individuals can give rise to many cell types, facilitating the study of mechanisms of development, human disease modeling, and early drug target validation. In this context, experimental model systems based on hiPSC-derived motor neurons (MNs) have been used to study MN diseases such as spinal muscular atrophy and amyotrophic lateral sclerosis. Modeling MN disease using hiPSC-based approaches requires culture conditions that can re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Moreover, the increased expression over time of proteins related to the synthesis and transport of the ACh, such as ChAT or VAChT and SV2 suggests a progressive improvement of the neurotransmission capacity that would require 40–50 days to be efficient. The firing rate that we detected in hFM-MSC-derived MNs even if not particularly high, was still comparable to that observed in hiPSC-derived MNs ( Smith et al., 2021 ; Thiry et al., 2022 ); but lower than that recorded in hiPSC-derived MNs co-cultured with astrocytes or in vivo (MNs isolated from animal spinal cord) ( Carp et al., 2008 ; Taga et al., 2019 ): this finding probably reflects the absence in our system of neurotrophic influences from glial cells or of the neuro-modulatory activity from afferent or descending inputs. In contrast with MEA studies utilizing cortical neurons ( Odawara et al., 2018 ; Di Credico et al., 2021 ), we did not detect the formation of physiologically relevant neural networks among spinal cord hFM-MSC-derived MNs.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the increased expression over time of proteins related to the synthesis and transport of the ACh, such as ChAT or VAChT and SV2 suggests a progressive improvement of the neurotransmission capacity that would require 40–50 days to be efficient. The firing rate that we detected in hFM-MSC-derived MNs even if not particularly high, was still comparable to that observed in hiPSC-derived MNs ( Smith et al., 2021 ; Thiry et al., 2022 ); but lower than that recorded in hiPSC-derived MNs co-cultured with astrocytes or in vivo (MNs isolated from animal spinal cord) ( Carp et al., 2008 ; Taga et al., 2019 ): this finding probably reflects the absence in our system of neurotrophic influences from glial cells or of the neuro-modulatory activity from afferent or descending inputs. In contrast with MEA studies utilizing cortical neurons ( Odawara et al., 2018 ; Di Credico et al., 2021 ), we did not detect the formation of physiologically relevant neural networks among spinal cord hFM-MSC-derived MNs.…”
Section: Discussionsupporting
confidence: 86%
“…In our experience, MNs in culture plated in Matrigel or poly-L-ornithine and laminin for up to 2 months start detaching. For this reason, the use of other coating substrates, such as dendritic polyglycerol amine ( Thiry et al, 2022 ), has been suggested to improve conditions for long-term cultures of iPSC-derived MNs.…”
Section: Challenges With Using Small Molecules That Require Further O...mentioning
confidence: 99%
“…Human iPSC line NCRM-1 was obtained from the National Institutes of Health Stem Cell Resource (Bethesda, MD, USA). Human iPSC lines CS52iALS-C9n6.ISOxx (referred to as “CS52” hereafter for sake of brevity) and CS29iALS-C9n1.ISOxx (“CS29” hereafter), corresponding to corrected, isogenic lines derived from two distinct parental lines generated from ALS patients with C9orf72 gene mutations, were obtained from Cedars-Sinai (Los Angeles, CA, USA) ( Thiry et al, 2022 ). Undifferentiated state of human iPSCs was assessed by testing for expression of the stem cell markers NANOG and OCT4 using rabbit anti-NANOG (1/1,000; Abcam; Cambridge, UK; Cat.…”
Section: Methodsmentioning
confidence: 99%